A Facile Strategy for the Preparation of MoS3 and its Application as a Negative Electrode for Supercapacitors. Issue 17 (17th August 2016) - Zhang, Tong; Kong, Ling‐Bin; Dai, Yan‐Hua; Yan, Kun; Shi, Ming; Liu, Mao‐Cheng; Luo, Yong‐Chun; Kang, Long
Abstract: Owing to their graphene‐like structure and available oxidation valence states, transition metal sulfides are promising candidates for supercapacitors. Herein, we report the application of MoS3 as a new negative electrode for supercapacitors. MoS3 was fabricated by the facile thermal decomposition of a (NH4 )2 MoS4 precursor. For comparison, samples of MoS3 &MoS2 and MoS2 were also synthesized by using the same method. Moreover, this is the first report of the application of MoS3 as a negative electrode for supercapacitors. MoS3 displayed a high specific capacitance of 455.6 F g −1 at a current density of 0.5 A g −1 . The capacitance retention of the MoS3 electrode was 92 % after 1500 cycles, and even 71 % after 5000 cycles. In addition, an asymmetric supercapacitor assembly of MoS3 as the negative electrode demonstrated a high energy density at a high potential of 2.0 V in aqueous electrolyte. These notable results show that MoS3 has significant potential in energy‐storage devices. Abstract : MoS Def : MoS3 has been prepared and employed as a new negative electrode for supercapacitors with excellent electrochemical performance.